Analisis Kesulitan Siswa Dalam Menyelesaikan Soal Matematika Materi Perbandingan Ditinjau Dari Tingkat Kemampuan Siswa Kelas VII SMP Negeri 1 Maluk Tahun Pelajaran 2020/2021 - Hairun Nufus; Sudi Prayitno; Baidowi Baidowi; Muhammad Turmuzi (Griya Journal of Mathematics Education and Application, 2022)
This study aims to describe the types of student’s difficulties in solving the mathematical problem material of comparison evaluated from the ability level of students class VII of SMPN 1 Maluk. The type of research is descriptive qualitative research. The population of this study was students of class VII SMPN 1 Maluk. In determining the sample, the proportionate stratified random sampling technique was used. The sample in this study were 20 students and were taken randomly. The data collection techniques used were test and interview. The results obtained from the research that for high ability students they have difficulties of 40,09%, with difficulties are, difficulty in multiplication and division operations, difficulty in determining the formula according to the question request, and have difficulty in drawing graphs. For medium ability students, they have difficulties of 70,31%, with difficulties are, difficulty in multiplication and division operations, difficulty in carrying out problem solving steps, difficulty in determining the formula according to the question request, and have difficulty in drawing graphs. For low ability students they have difficulties of 84,82%, with difficulties are, difficulty in multiplication and division operations, difficulty in carrying out problem solving steps, difficulty in determining the formula according to the question request, and have difficulty in understanding and drawing graphs.